2011
DOI: 10.1177/0013164410390032
|View full text |Cite
|
Sign up to set email alerts
|

Applying Item Response Theory Methods to Examine the Impact of Different Response Formats

Abstract: In aptitude and achievement tests, different response formats are usually used. A fundamental distinction must be made between the class of multiple-choice formats and the constructed response formats. Previous studies have examined the impact of different response formats applying traditional statistical approaches, but these influences can also be studied using methods of item response theory to deal with incomplete data. Response formats can influence item attributes in two ways: different response formats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…As Table 13 shows, no significant differences were found. Similar to earlier findings by Hohensinn and Kubinger (2011) and In'nami and Koizumi (2009), the CR items seemed slightly more difficult.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As Table 13 shows, no significant differences were found. Similar to earlier findings by Hohensinn and Kubinger (2011) and In'nami and Koizumi (2009), the CR items seemed slightly more difficult.…”
Section: Discussionsupporting
confidence: 88%
“…Given this correlation, both the CR and the MC formats appear to measure the same latent trait to a great extent, but the formats may elicit different skills and/or assess skills differently (cf. Hohensinn & Kubinger, 2011;Lissitz & Hou, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Current practices in low-stakes educational large-scale achievement tests involve treating unplanned missing values as incorrect or fractionally correct responses or ignoring them in the scaling (see, e.g., PISA, Adams & Wu, 2002;TIMSS [Third International Mathematics and Science Study], Martin, Gregory, & Stemler, 2000; NAEP [National Assessment of Educational Progress], Allen, Donoghue, & Schoeps, 2001;NEPS [National Educational Panel Study], Pohl & Carstensen, 2012). Research on these types of missing data approaches showed bias on item and person parameter estimates when missing values were scored as incorrect (Culbertson, 2011;De Ayala, Plake, & Impara, 2001;Finch, 2008;Hohensinn & Kubinger, 2011;Holman & Glas, 2005;Pohl, Gräfe, & Rose, 2014;Rose et al, 2010). The method of fractionally correct scoring performed slightly better but also resulted in bias, especially when missing values were MNAR (De Ayala et al, 2001;Finch, 2008).…”
mentioning
confidence: 99%
“…The Rasch testlet model yields itself very well to modeling LID due to its common method. Instead of forming group factors based on common passages we build them based on common test formats (Hohensinn & Kubinger, 2011). That is, each item is forced to load on a target ability dimension and its pertinent method dimension.…”
mentioning
confidence: 99%